2021
DOI: 10.3389/fpls.2021.644810
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Data Integration of Wheat Cultivars Facing Fusarium graminearum Strains Revealed a Core-Responsive Pattern Controlling Fusarium Head Blight

Abstract: Fusarium head blight (FHB), mainly occurring upon Fusarium graminearum infection in a wide variety of small-grain cereals, is supposed to be controlled by a range of processes diverted by the fungal pathogen, the so-called susceptibility factors. As a mean to provide relevant information about the molecular events involved in FHB susceptibility in bread wheat, we studied an extensive proteome of more than 7,900 identified wheat proteins in three cultivars of contrasting susceptibilities during their interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 119 publications
4
4
0
Order By: Relevance
“…The prediction of their subcellular localization in the host cell demonstrated that the chloroplast could be a primary target of F. graminearum effectors, followed by the plant nucleus. Although functional characterizations of these proteins might be necessary to identify their intracellular localization and their role in the infection process, this clearly corroborates previous dual-proteomics on the FHB disease in bread wheat that identified a close relationship between chloroplast adjustments and the accumulation of F. graminearum proteins harboring the features of a chloroplast transit peptide [17,56,78]. Among SPCs with known functions, more than 70% are closely linked to plant/pathogen interaction and pathogenicity, including CAZymes, proteases and PHI genes.…”
Section: Links Between the Genetic Variations In F Graminearum Secretomes And The Strain Aggressiveness In Wheat Tissuessupporting
confidence: 86%
See 1 more Smart Citation
“…The prediction of their subcellular localization in the host cell demonstrated that the chloroplast could be a primary target of F. graminearum effectors, followed by the plant nucleus. Although functional characterizations of these proteins might be necessary to identify their intracellular localization and their role in the infection process, this clearly corroborates previous dual-proteomics on the FHB disease in bread wheat that identified a close relationship between chloroplast adjustments and the accumulation of F. graminearum proteins harboring the features of a chloroplast transit peptide [17,56,78]. Among SPCs with known functions, more than 70% are closely linked to plant/pathogen interaction and pathogenicity, including CAZymes, proteases and PHI genes.…”
Section: Links Between the Genetic Variations In F Graminearum Secretomes And The Strain Aggressiveness In Wheat Tissuessupporting
confidence: 86%
“…These represented a total of 18 spikelets per plant (90 measurements per strain) that were individually scored for the symptom dynamics at 72 h after the inoculation (hpi). This duration was chosen on the basis of our previous studies [17,56,78] demonstrating a turning point in the FHB progress at this time, enabling to discriminate strains of contrasted aggressiveness. Along with the forty infected plants, five additional ones were inoculated with water and were used as a control, and no symptoms were observed on these plants.…”
Section: Fusarium Graminearum Isolates and Strain Aggressiveness Ratingmentioning
confidence: 99%
“…The search for localization signals within the F. graminearum secreted protein sequences revealed that putative effectors can target host apoplast, as well as different subcellular compartments including nucleus, chloroplast and mitochondria at several infection stages (Figure 7). Along with the relatively high diversity of predicted functions (66 GO terms and 140 Pfam), this supports that the infection success is based on a wide array of manipulated host pathways and echoes previous studies that evidenced the diverse nature of processes involved in FHB susceptibility [19,20,23].…”
Section: F Graminearum Infection Strategy Involves Integrative Host C...supporting
confidence: 83%
“…The inhibition of the defense mechanisms through the manipulation of chloroplast [76] and mitochondrial [77] processes was already evidenced in several plant-fungi interactions and proved here to be part of the F. graminearum infection strategy. In the case of the chloroplast, its central role has already been described in previous FHB studies [19,20,23]. Finally, effectors with multiple host targets were also detected, suggesting that one effector can achieve completely different functions during the infection progress.…”
Section: F Graminearum Infection Strategy Involves Integrative Host C...supporting
confidence: 63%
See 1 more Smart Citation